Profile of natural anticoagulant, coagulant factor and anti-phospholipid antibody in critically ill COVID-19 patients - Zhang, Yan; Cao, Wei; Jiang, Wei; Xiao, Meng; Li, Yongzhe; Tang, Ning; Liu, Zhengyin; Yan, Xiaowei; Zhao, Yongqiang; Li, Taisheng; Zhu, Tienan (Journal of thrombosis and thrombolysis, 2020)
The outbreak of novel coronavirus disease 2019 (COVID-19) has now become a global pandemic. Coagulopathy has been reported widely in critically ill COVID-19 patients and was related to high mortality. However, the comprehensive coagulation profiles have not been examined and the underlying mechanism of the coagulopathy in COVID-19 patients is unclear. To study the coagulation profiles of routine hemostasis tests, natural anticoagulants, coagulant factors and antiphospholipid antibodies in critically ill COVID-19 patients. This single-center and cross-section study included 19 patients with COVID-19, who were admitted to intensive care unit (ICU) at Tongji hospital in Wuhan, China, from Feb 23 to Mar 3, 2020. Demographic data, laboratory parameters, treatments and clinical outcomes of the patients were collected and analyzed. The final date of follow-up was Mar 31, 2020. In this study, 12 thrombotic events occurred in 9 patients, including 4 cerebral infarctions, 7 acro-ischemia and 1 internal jugular vein thrombosis. The common abnormalities of routine coagulation tests included evelated D-Dimer level (100%), prolonged prothrombin time (73.7%) and hyperfibrinogenemia (73.7%). The median activities of natural anticoagulants including protein C, protein S and antithrombin were all below the normal range. Factor VIII activities were significantly above normal range (median value 307%, IQR 198–441) in all patients. Factor V and factor VII activities were significantly lower in near-terminal stage patients. Anti-phospholipid antibodies were present in 10 patients. Strikingly, 4 cerebral infarction events were in patients had anti-phospholipid antibodies of multiple isotypes. Sustained hypercoagulable status and thrombotic events were common in critically ill patients with COVID-19. The low activities of natural anticoagulants, elevated factor VIII level and the presence of antiphospholipid antibodies, together, may contribute to the etiopathology of coagulopathy in COVID-19 patients.